Penggunaan ponsel pintar sebagai faktor risiko terjadinya nyeri kepala primer pada mahasiswa kedokteran Untan - Kim Liung; Ery Hermawati; Willy Handoko (Majalah Kedokteran Andalas, 2023)
Headache is one of the common symptoms found in nervous system disorders. The incidence of headache in the world in adult humans is 50% in the population with various headache categories. Previous research has shown that there is a relationship between smartphone use and musculoskeletal disorders in the neck, shoulders and hands in young adults. One of the groups involved in the use of smart phones is students. Objective: The purpose of this study was to determine the relationship between the use of smart phones and other factors that cause primary headaches, with the incidence of primary headaches in medical students of Untan. Methods: Observational analytic study of cross-sectional type. The research population is the students of the Untan Medical Study Program, who were selected using a side stratified random technique. Bivariate analysis using contingency coefficient test. Results: The results of the contingency coefficient analysis test showed a p-value of 0.038 (Sig <0.05) for the relationship between the intensity of smartphone use and primary headache, and a p-value >0.05 for the relationship between all other factors and primary headaches. Conclusion: There is a relationship between the intensity of smartphone use on primary headaches in Untan medical students.